Speculators, prices and market volatility - Celso Brunetti; Bahattin Büyükşahin; Jeffrey Harris (Bank of Canada, 2015)
We analyze data from 2005 through 2009 that uniquely identify categories of traders to assess how speculators such as hedge funds and swap dealers relate to volatility and price changes. Examining various subperiods where price trends are strong, we find little evidence that speculators destabilize financial markets. To the contrary, hedge funds facilitate price discovery by trading with contemporaneous returns while serving to reduce volatility. Swap dealer activity, however, is largely unrelated to both contemporaneous returns and volatility. Our evidence is consistent with the hypothesis that hedge funds provide valuable liquidity and largely serve to stabilize futures markets.
Keywords: C3; G1; 330; International topics; Recent economic and financial developments